Plant stable isotope composition across habitat gradients in a semi‐arid savanna: implications for environmental reconstruction - JACQUELINE CODRON; JULIA A. LEE‐THORP; MATT SPONHEIMER; DARYL CODRON (Journal of Quaternary Science, 2013)
Field studies of plant stable carbon and nitrogen isotope composition have revealed relationships with temperature and precipitation. These relationships conform to theoretical predictions of how extrinsic factors impact on ecophysiological processes such as photosynthesis and nitrogen cycling. However, examination of many datasets reveals high levels of variation, especially across environments with moderate precipitation ( −1 ). To test for extrinsic effects on plant isotope composition in such environments, we studied data from plants collected over three years from multiple habitats and seasons in Kruger National Park, South Africa. Our sample is sufficiently large to evaluate not only effects of environmental variables (rainfall up to ∼800 mm a −1 , temperature, physical habitat structure) but also taxonomic effects. Species composition of habitats accounted for most of the variation in our data, followed by physical habitat structure (e.g. wooded or riverine compared with open, grassy habitats), while rainfall and temperature had only indirect or negligible effects. The latter finding concurs with subsections of existing datasets and we suggest therefore that such effects usually become visible in datasets that span environmental extremes, implying environmental ranges within which plant isotope variations cannot readily be ascribed to climate. Copyright © 2013 John Wiley & Sons, Ltd.

Landscape-scale feeding patterns of African elephant inferred from carbon isotope analysis of feces - Jacqueline Codron; Daryl Codron; Julia A. Lee-Thorp; Matt Sponheimer; Kevin Kirkman; Kevin J. Duffy; Judith Sealy (Oecologia, 2011)